Organization of the System of Internal Marketing and Marketing of Interaction of Agricultural Enterprises for the Production of Biodiesel Based on Value Chain Analysis - LOHOSHA, Roman; PRYLUTSKYI, Anatolii; PRONKO, Lyudmila; KOLESNYK, Tetiana (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
The aim of the study was to analyze and evaluate the organization of the system of internal marketing and marketing interaction of agricultural enterprises for the production of biodiesel based on value chain analysis. The authors conducted aresearch on the formation of a marketing model and the corresponding marketing policy of the enterprise, where it is methodologically important is the formation of effective value chains as a basis for competition in the market. The theoretical approach to the formation of the value chain within the marketing model of an individual agricultural enterprise is substantiated. At the same time, value chains are seen as production networks in which businesses use competitive resources and operate in an institutional environment, and form network of horizontally and vertically connected enterprises united by a partnership model of interaction. The objectives of the study were solved using such methods as: historical, systematic, inductive and deductive, analysis and synthesis, modeling and comparative analysis. To ensure the efficiency of energy production from biomass, the optimality of the logistics factor should be ensured. Applied models based on tools such as operations research and mathematical optimization using computer algorithms have been developed to plan and manage biomass supply chains. It is proposed to model supply chains and / or create value by types of resource flows with the possibility of their modular connection to the overall model, which, in our opinion, can increase the reliability of the results. To study the value chain of biodiesel in Ukraine, an appropriate model was developed to simulate the flow of raw sunflower and rapeseed, as the use of both crops was identified as the most common for biodiesel production in Ukraine. The model differs from the existing ones in that it takes into account different scenarios to determine the total cost of biodiesel production, as well as the cost of individual activities in the value chain formation.